2013
DOI: 10.1002/adfm.201203675
|View full text |Cite
|
Sign up to set email alerts
|

Red, Green, and Blue Light‐Emitting Polyfluorenes Containing a Dibenzothiophene‐S,S‐Dioxide Unit and Efficient High‐Color‐Rendering‐Index White‐Light‐Emitting Diodes Made Therefrom

Abstract: A series of blue (B), green (G) and red (R) light-emitting, 9,9-bis(4-(2-ethylhexyloxy)phenyl)fl uorene (PPF) based polymers containing a dibenzothiophene-S,S -dioxide (SO) unit (PPF-SO polymer), with an additional benzothiadiazole (BT) unit (PPF-SO-BT polymer) or a 4,7-di(4-hexylthien-2-yl)benzothiadiazole (DHTBT) unit (PPF-SO-DHTBT polymer) are synthesized. These polymers exhibit high fl uorescence yields and good thermal stability. Light-emitting diodes (LEDs) using PPF-SO25, PPF-SO15-BT1, and PPF-SO15-DHTB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(69 citation statements)
references
References 67 publications
0
65
0
2
Order By: Relevance
“…6) [24]. In this case white light stability has been attributed to the fact that the three copolymers have very similar chemical structures and do not show tendency to crystallization and phase separation.…”
Section: Approach (2): Woleds Bearing Multiple Emitters In a Single Lmentioning
confidence: 98%
“…6) [24]. In this case white light stability has been attributed to the fact that the three copolymers have very similar chemical structures and do not show tendency to crystallization and phase separation.…”
Section: Approach (2): Woleds Bearing Multiple Emitters In a Single Lmentioning
confidence: 98%
“…Additional opportunities are provided by other CP classes. A good example here is provided by the blue, green and red light‐emitting CPs based on 9,9‐bis(4‐(2‐ethylhexyloxy)phenyl)fluorene containing a dibenzothiophene‐ S,S ‐dioxide unit with additional benzothiadiazole or 4,7‐di(4‐hexylthien‐2‐yl)‐benzothiadiazole moieties . Besides good thermal stability, these polymers show high FL yields, rendering them promising candidates for OLED fabrication.…”
Section: Controlling the Emission Properties Of Conjugated Polymers Bmentioning
confidence: 99%
“…Previously, time-of-flight (TOF) mobility measurements revealed that thermally stable SO-based derivatives have high electron mobility of 10 À4 -10 À3 cm 2 V À1 S À1 [21,22]. Due to the excellent electron-inject/transport property of SO units, recently, Yu et al reported highly efficient double-layer blue OLEDs with CE max of 7 cd/A through utilizing polyfluorene containing SO units and poly(N-vinylcarbazole) (PVK) as an EML and HTL, respectively [20].…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, it is also difficult to inject electrons from the cathode in blue OLEDs due to the large energy band gaps of the fluorene-based emitters. To enhance the electron injection and transport, with an introduction of electron-withdrawing components, for example, dibenzothiophene-S,S-dioxide (SO) units, into the polymers or oligomers is proven to be effective [16][17][18][19][20]. Previously, time-of-flight (TOF) mobility measurements revealed that thermally stable SO-based derivatives have high electron mobility of 10 À4 -10 À3 cm 2 V À1 S À1 [21,22].…”
Section: Introductionmentioning
confidence: 99%